2021
DOI: 10.3390/vaccines9101129
|View full text |Cite
|
Sign up to set email alerts
|

Nanotechnology Interventions in the Management of COVID-19: Prevention, Diagnosis and Virus-Like Particle Vaccines

Abstract: SARS-CoV-2 claimed numerous lives and put nations on high alert. The lack of antiviral medications and the small number of approved vaccines, as well as the recurrence of adverse effects, necessitates the development of novel treatment ways to combat COVID-19. In this context, using databases such as PubMed, Google Scholar, and Science Direct, we gathered information about nanotechnology’s involvement in the prevention, diagnosis and virus-like particle vaccine development. This review revealed that various na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(9 citation statements)
references
References 149 publications
(180 reference statements)
0
8
0
Order By: Relevance
“…Lipid-coated MSNPs containing antiviral agent (ML336) were developed as a strategy to improve antiviral circulation time and biocompatibility. In vitro results revealed a dose-dependent virus inhibition and an additional release of ML336 after cell endocytosis, while in vivo results showed that NPs showed significant antiviral activity and no toxicity (Siddiquie et al, 2020;Balkrishna et al, 2021;Duan et al, 2021).…”
Section: Nanomaterial-based Drug Delivery Systemsmentioning
confidence: 96%
“…Lipid-coated MSNPs containing antiviral agent (ML336) were developed as a strategy to improve antiviral circulation time and biocompatibility. In vitro results revealed a dose-dependent virus inhibition and an additional release of ML336 after cell endocytosis, while in vivo results showed that NPs showed significant antiviral activity and no toxicity (Siddiquie et al, 2020;Balkrishna et al, 2021;Duan et al, 2021).…”
Section: Nanomaterial-based Drug Delivery Systemsmentioning
confidence: 96%
“…However, the cytotoxicity of AuNPs is affected by surface charge, size, shape, and surface modification, and modified AuNPs may be toxic to cells. [39] The precious metal gold is expensive and costly to use as an antimicrobial agent. The reported gold nanoparticle-loaded hydrogels are not really considered to be simple to prepare, inexpensive, with long-lasting antibacterial effect and biodegradability, which are some distance away from the practical application to biomedical aspects and need to continue to study this side.…”
Section: Biomedical Potential Of Gold-loaded Antibacterial Hydrogelmentioning
confidence: 99%
“…Thereafter, focusing on all these serious toxicities along with intolerable adverse effects of recommended drugs and vaccines for COVID 19, full attention has been gained towards the development of novel Nano-technological based delivery. Nanotechnologies with a great significance specifying the characteristics of rapid and accurate diagnosis, target-specific delivery with reduced dosing frequency and hence toxicities, combinatorial therapy, tunable drug release, biocompatibility, low immunogenicity, multidrug delivery with high selectivity and specificity make the nano therapeutic strategy more significant over conventional delivery as shown in Figure 4 [77] , [78] , [79] . In this review, we broadly investigated the current approach and future possibilities of a nano-technological based approach for diagnosis, delivery of potential Anti-COVID 19 therapeutic moieties and vaccine delivery as well.…”
Section: Current Inline Treatmentmentioning
confidence: 99%